Influence of VAM fungi on growth of jackfruit (Artocarpus heterophyllus L.) cv. Rudrakshi, soil parameters and microbial population of soil (Indian Journal of Arid Horticulture, 2025)
The soil application of various VAM treatments significantly influenced the growth of jackfruit (Artocarpus heterophyllus L.) cv. Rudrakshi. Among the treatments, T6 (RDF + 70g VAM) was found to be significantly superior to all others with respect to plant growth and soil parameters. T6 recorded the highest plant height (1.40 m), plant girth (148.42 mm), number of leaves per shoot (48.00) and number of shoots per plant (29.67). In addition, it also resulted in improved soil characteristics, including optimal pH (7.23) and population of fungi (10.67 × 10³ cfu g-¹).